The internal deformation of the Peridotite Nappe of New Caledonia: A structural study of serpentine-bearing faults and shear zones in the Koniambo Massif. (April 2016) - Quesnel, Benoît; Gautier, Pierre; Cathelineau, Michel; Boulvais, Philippe; Couteau, Clément; Drouillet, Maxime
Abstract: We present a structural analysis of serpentine-bearing faults and shear zones in the Koniambo Massif, one of the klippes of the Peridotite Nappe of New Caledonia. Three structural levels are recognized. The upper level is characterized by a dense network of fractures. Antigorite and polygonal serpentine form slickenfibers along fault planes with distinct kinematics. As a result, the upper level keeps the record of at least two deformation events, the first associated with the growth of antigorite (WNW-ESE extension), the second with the growth of polygonal serpentine (NW–SE compression). The lower level coincides with the 'serpentine sole' of the nappe, which consists of massive tectonic breccias overlying a layer of mylonitic serpentinites. The sole records pervasive tangential shear with top-to-SW kinematics and represents a décollement at the base of the nappe. The intermediate level is characterized by the presence of several meters-thick conjugate shear zones accommodating NE–SW shortening. Like the sole, these shear zones involve polygonal serpentine and magnesite as the main syn-kinematic mineral phases. The shear zones likely root into the basal décollement, either along its roof or, occasionally, around its base. Compared to top-to-SW shearing along the sole, the two deformation events recorded in the upper level are older. The three structural levels correlate well with previously recognized spatial variations in the degree of serpentinization. It is therefore tempting to consider that the intensity of serpentinization played a major role in the way deformation has been distributed across the Peridotite Nappe. However, even the least altered peridotites, in the upper level, contain so much serpentine that, according to theoretical and experimental work, they should be nearly as weak as pure serpentinite. Hence, no strong vertical gradient in strength due to variations in the degree of serpentinization is expected within the exposed part of the nappe. Our proposal is that strain localization along the serpentine sole results from the juxtaposition of the nappe, made of weak serpentinized peridotites, against the strong mafic rocks of its substratum. This interpretation is at odds with the intuitive view that would consider the nappe, made of peridotites, as stronger than its basement. Highlights: We study the deformation associated with serpentines in the New Caledonia ophiolite. Structural analysis is coupled with mineralogical characterization. The evolution of deformation through space and time is described. The reason for strain localization along the sole of the nappe is discussed.